TINJAUAN YURIDIS TANGGUNG JAWAB NEGARA PENERIMA DALAM TINDAK PIDANA PERDAGANGAN ORANG BERDASARKAN UNITED NATIONS CONVENTION AGAINST TRANSNATIONAL ORGANIZED CRIME PALERMO 2000 (Studi Tentang Perdagangan Tenaga Kerja Indonesia Ilegal Melalui Situs Daring Carousell Singapura) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Human trafficking as an transnational organized crime is giving responsibilityfor the state not only to punish the perpetrators,but also for victims of trafficking inperson. The form of responsibility of the Receiving States of victims of trafficking underthe Palermo Convention 2000 is to provide assistance and protection to victims while intheir territory. Placement of TKI abroad is one mode that can be applied byirresponsible individuals to ensnare victims. One of the cases that has occured istrafficking in illegal TKI through the Singapore's Carousell online site.The type of research conducted is normative-juridical research on systematic oflaw, which is to identify the basic understanding or basis of rights and obligations,legal events, legal relations, and legal objects. In this research, data source used issecondary data with primary law material, secondary, and tertiary law material whichdone by library research.From the result of the research it is found that, first Singapore is responsible fordisciplining its citizens in order to prevent the existence of perpetrators and victims oftrafficking in persons. Second, Indonesian regulations have sufficiently fulfilled therights of assistance and protection for victims of trafficking. While Singapore'sregulations regarding this matter are considered not sufficient to meet the provisions ofthe convention, such as the right to obtain information, physical security, compensation,and also the return of victims of trafficking.Keywords: States Responsibility-Trafficking in person-Transnational OrganizedCrime-TKI